Noen tanker om norsk-polsk og polsk-norsk ordboksarbeid - Skommer, Grzegorz (Folia Scandinavica Posnaniensia, 2007)
The paper provides a brief overview of the existing Norwegian-Polish and Polish-Norwegian dictionaries. It also reports on prospective lexicographical work and gives a detailed presentation of a Polish- Norwegian dictionary which is currently being compiled at the Department of Scandinavian and Baltic Studies of the Adam Mickiewicz University in Poznan.